Analisis Penggunaan Internet Sebagai Referensi Mahasiswa Stain Curup (Studi Manfaat dan Dampak Media Massa) - Komalasari, Bakti; Naumi, Adinda Tessa (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study is a study focused on finding meaning towards the behavior of internet usage as reference of STAIN Curup students. In line with the concept of an active audience, this research would focus on the internet as a mass media. With the advancement of information technology and mass media, providing various facilities in accessing information especially through the internet. STAIN Curup students are required to keep updating their knowledge and information especially with regard to their studies. This need is what makes the student must continue to add the supporting reference study. In addition to books, print journals and modules, the internet becomes one of the reference sources used by students. Therefore, it needs to be studied further about how the use of internet as a reference STAIN Curup students? how is the impact of internet use as a reference of STAIN Curup students? To answer the problems, this research uses the uses and gratifications theory and the moderate effect model, which is expected to give meaning and peel the phenomenon of internet usage on the students. In line with the uses and gratifications theory, satisfaction will arise if needs are met. In this case, the satisfaction of internet usage as reference of student is seen from the functioning of mass media, among others: information function, entertainment function, persuasion function, cultural transmission function and social inheritance, correlation function (linking). While the impact of internet use as a reference of students, among others, cognitive impact, affective impact, and behavioral impact. The impact of internet usage is also supported by individual factors; such as selective attention, selective perception, and selective retention, motivation and knowledge, beliefs, opinions, values, and needs, persuasion, personality and adjustment. And social factors, among others; age, sex, education and training, occupation and income, religion, residence.